Westonci.ca is the trusted Q&A platform where you can get reliable answers from a community of knowledgeable contributors. Get quick and reliable solutions to your questions from knowledgeable professionals on our comprehensive Q&A platform. Join our Q&A platform to connect with experts dedicated to providing accurate answers to your questions in various fields.
Sagot :
To determine how [tex]\( f(x) \)[/tex] was transformed to create [tex]\( g(x) \)[/tex], we need to analyze the corresponding [tex]\( y \)[/tex]-values for each [tex]\( x \)[/tex]-value in the given tables.
Let's set up the values:
For [tex]\( f(x) \)[/tex]:
- [tex]\( f(-2) = \frac{1}{9} \)[/tex]
- [tex]\( f(-1) = \frac{1}{3} \)[/tex]
- [tex]\( f(2) = 9 \)[/tex]
- [tex]\( f(3) = 27 \)[/tex]
- [tex]\( f(4) = 81 \)[/tex]
For [tex]\( g(x) \)[/tex]:
- [tex]\( g(-2) = -\frac{17}{9} \)[/tex]
- [tex]\( g(-1) = -\frac{5}{3} \)[/tex]
- [tex]\( g(2) = 7 \)[/tex]
- [tex]\( g(3) = 25 \)[/tex]
- [tex]\( g(4) = 79 \)[/tex]
Next, we calculate the differences between the corresponding [tex]\( y \)[/tex]-values of [tex]\( g(x) \)[/tex] and [tex]\( f(x) \)[/tex]:
1. For [tex]\( x = -2 \)[/tex]:
[tex]\[ g(-2) - f(-2) = -\frac{17}{9} - \frac{1}{9} = -\frac{17 + 1}{9} = -\frac{18}{9} = -2 \][/tex]
2. For [tex]\( x = -1 \)[/tex]:
[tex]\[ g(-1) - f(-1) = -\frac{5}{3} - \frac{1}{3} = -\frac{5 + 1}{3} = -\frac{6}{3} = -2 \][/tex]
3. For [tex]\( x = 2 \)[/tex]:
[tex]\[ g(2) - f(2) = 7 - 9 = -2 \][/tex]
4. For [tex]\( x = 3 \)[/tex]:
[tex]\[ g(3) - f(3) = 25 - 27 = -2 \][/tex]
5. For [tex]\( x = 4 \)[/tex]:
[tex]\[ g(4) - f(4) = 79 - 81 = -2 \][/tex]
Observe that the difference between [tex]\( g(x) \)[/tex] and [tex]\( f(x) \)[/tex] is consistently [tex]\(-2\)[/tex] for all [tex]\( x \)[/tex]-values.
The consistent difference of [tex]\(-2\)[/tex] indicates that [tex]\( g(x) \)[/tex] was obtained by vertically shifting [tex]\( f(x) \)[/tex] downwards by 2 units.
Thus, the correct transformation is:
[tex]\[ \boxed{D. \text{Horizontal or vertical shift}}\][/tex]
Let's set up the values:
For [tex]\( f(x) \)[/tex]:
- [tex]\( f(-2) = \frac{1}{9} \)[/tex]
- [tex]\( f(-1) = \frac{1}{3} \)[/tex]
- [tex]\( f(2) = 9 \)[/tex]
- [tex]\( f(3) = 27 \)[/tex]
- [tex]\( f(4) = 81 \)[/tex]
For [tex]\( g(x) \)[/tex]:
- [tex]\( g(-2) = -\frac{17}{9} \)[/tex]
- [tex]\( g(-1) = -\frac{5}{3} \)[/tex]
- [tex]\( g(2) = 7 \)[/tex]
- [tex]\( g(3) = 25 \)[/tex]
- [tex]\( g(4) = 79 \)[/tex]
Next, we calculate the differences between the corresponding [tex]\( y \)[/tex]-values of [tex]\( g(x) \)[/tex] and [tex]\( f(x) \)[/tex]:
1. For [tex]\( x = -2 \)[/tex]:
[tex]\[ g(-2) - f(-2) = -\frac{17}{9} - \frac{1}{9} = -\frac{17 + 1}{9} = -\frac{18}{9} = -2 \][/tex]
2. For [tex]\( x = -1 \)[/tex]:
[tex]\[ g(-1) - f(-1) = -\frac{5}{3} - \frac{1}{3} = -\frac{5 + 1}{3} = -\frac{6}{3} = -2 \][/tex]
3. For [tex]\( x = 2 \)[/tex]:
[tex]\[ g(2) - f(2) = 7 - 9 = -2 \][/tex]
4. For [tex]\( x = 3 \)[/tex]:
[tex]\[ g(3) - f(3) = 25 - 27 = -2 \][/tex]
5. For [tex]\( x = 4 \)[/tex]:
[tex]\[ g(4) - f(4) = 79 - 81 = -2 \][/tex]
Observe that the difference between [tex]\( g(x) \)[/tex] and [tex]\( f(x) \)[/tex] is consistently [tex]\(-2\)[/tex] for all [tex]\( x \)[/tex]-values.
The consistent difference of [tex]\(-2\)[/tex] indicates that [tex]\( g(x) \)[/tex] was obtained by vertically shifting [tex]\( f(x) \)[/tex] downwards by 2 units.
Thus, the correct transformation is:
[tex]\[ \boxed{D. \text{Horizontal or vertical shift}}\][/tex]
We appreciate your time on our site. Don't hesitate to return whenever you have more questions or need further clarification. We appreciate your visit. Our platform is always here to offer accurate and reliable answers. Return anytime. Westonci.ca is your trusted source for answers. Visit us again to find more information on diverse topics.